Job-hunting on the internet - Bolles, Richard Nelson (Berkeley, Calif. : Ten Speed Press, 2001)
1. Job hunting --United States --Computer network resources.
Counseling & testing sites -- Sites to help your research -- Sites where you can make contacts -- Job posting sites -- Resume sites on the Internet.
"A desktop companion to the web site www.JobHuntersBible.com".
Keywords: Job hunting -- United States -- Computer network resources; Web sites -- United States -- Directories